The Model of Academic Administration under the Iddhipada 4 of School administrators within the Roi Et Primary Educational Service Area Office 2 - Pangkul, Pathinya; Moeithaisong, Suthep (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research are 1) to study the current situation, desirable conditions, and necessary requirements for managing academic work according to the Iddhipada 4 of educational administrators under the Roi Et Primary Educational Service Area Office 2, 2) to establish a model for managing academic work based on the Iddhipada 4 of educational administrators, and 3) to evaluate the model of managing academic work based on the Iddhipada 4 principles of educational administrators as a mixed-method research. The sample group consists of a total of 351 teaching personnel. The data collection instruments used include questionnaires and assessments of suitability and feasibility. The content validity ranges from 0.67 to 1.00, and the reliability coefficient is 0.75. Data analysis was performed using standardized software to calculate percentages, means, standard deviations, and the PNImodified technique. The results show that: 1) The current state of academic management based on the Iddhipada 4 of educational administrators is generally at a moderate level, both overall and in specific areas. The desired state, on the other hand, is at a high level, both overall and in specific areas. The most important need is in the area of teaching and learning management, with a PNImodified index of 0.38, ranking as the first aspect, followed by innovative media and educational technology development, curriculum organization, promoting the establishment of learning sources, measurement, evaluation, credit transfer of learning outcomes, and educational guidance and counseling. 2) The model of academic management based on the Iddhipada 4 of educational administrators consists of six aspects which are teaching and learning management, development of innovative media and educational technology, curriculum development, promotion of learning sources, measurement, evaluation, and implementation of credit transfer for learning outcomes, and educational guidance and counseling. 3) The results of the evaluation of the academic administration model according to the principle of Iddhipada 4 of educational institute administrators found that the model was appropriate and possible at the highest level. It can be applied to develop academic administration effectively.